2017
DOI: 10.3390/scipharm85010012
|View full text |Cite
|
Sign up to set email alerts
|

n-Hexane Insoluble Fraction of Plantago lanceolata Exerts Anti-Inflammatory Activity in Mice by Inhibiting Cyclooxygenase-2 and Reducing Chemokines Levels

Abstract: Inflammation is involved in the progression of many disorders, such as tumors, arthritis, gastritis, and atherosclerosis. Thus, the development of new agents targeting inflammation is still challenging. Medicinal plants have been used traditionally to treat various diseases including inflammation. A previous study has indicated that dichloromethane extract of P. lanceolata leaves exerts anti-inflammatory activity in an in vitro model. Here, we examined the in vivo anti-inflammatory activities of a n-hexane ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
1
9
0
1
Order By: Relevance
“…Interestingly, ursolic acid reduced the MCP-1 level with a higher potency than IL-8. This result was in line with the previous study demonstrating that MCP-1 is the main chemokine responsible for leukocyte migration (Fakhrudin et al, 2017;Takahashi et al, 2009). This suggests that ursolic acid might be further examined for its efficacy against inflammatoryrelated diseases in which MCP-1 plays crucial roles such as diabetic nephropathy (Tesch, 2008), cardiovascular diseases (Epstein et al, 2009), rheumatoid arthritis (Ellingsen et al, 2000), and angiogenesis (Chang et al, 2005).…”
Section: Percentage Of Leukocyte Migrationsupporting
confidence: 91%
See 3 more Smart Citations
“…Interestingly, ursolic acid reduced the MCP-1 level with a higher potency than IL-8. This result was in line with the previous study demonstrating that MCP-1 is the main chemokine responsible for leukocyte migration (Fakhrudin et al, 2017;Takahashi et al, 2009). This suggests that ursolic acid might be further examined for its efficacy against inflammatoryrelated diseases in which MCP-1 plays crucial roles such as diabetic nephropathy (Tesch, 2008), cardiovascular diseases (Epstein et al, 2009), rheumatoid arthritis (Ellingsen et al, 2000), and angiogenesis (Chang et al, 2005).…”
Section: Percentage Of Leukocyte Migrationsupporting
confidence: 91%
“…NF-ĸB represents a promising target in inflammation and this protein regulate the production of pro-inflammatory cytokines and mediate inflammatory development. In the previous study, we found that the n-hexane insoluble fraction (HIF) of P. lanceolata dichloromethane extract is the active fraction with anti-inflammatory activity in mice (Fakhrudin et al, 2017). In this study, we isolated the major compound from the HIF and evaluated its anti-inflammatory activity by employing thioglycollate-induced mice peritonitis as pharmacological evidence.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Подорожник является одним из 200 наиболее хорошо охарактеризованных и описанных видов семейства Plantaginaceae и официнальным фармацевтическим средством в Европейской фармакопее [16]. Основные активные фармацевтические ингредиенты листьев подорожника (каталпол, аукубин и актеосайд) относятся к группе фенилэтаноидных и иридоидных гликозидов, обеспечивают противовоспалительный [12], антиоксидантный [13,36], иммуномодулирующий [18], а также ряд других эффектов [20,29].…”
Section: характеристика растительных препаратов эвкабал сироп и эвкабunclassified